Investigation on the effects of total organic carbon content and maturity of coal measure shale on biomethane production performance in the anaerobic digestion system - Qianwen RUAN; Qian WANG; Xianbo SU; Weizhong ZHAO; Fubo GAO (Meitan xuebao, 2024)
Coal measure shale gas is an important component of coal measure gas, and it is rich in in-situ microorganisms and dispersed organic matter required for microbial metabolism, making it possible to produce biomethane through anaerobic digestion, and providing supplements for the recoverable resources during coal measure gas development. However, the systematic studies on the methanogenesis mechanism of coal measure shale in the anaerobic digestion system are still limited, and the characteristics of biological methane production and its controlling factors remain unclear, which hinders its development and application. Coal measure shales from different regions were selected as the research object, and the in-situ microorganisms were enriched as the experimental microorganisms. Through some anaerobic digestion experiments, the biomethane production potential of the coal measure shales as well as the effects of total organic carbon (TOC) content and maturity (Ro) on the methanogenesis were studied. The results show that coal measure shales generally possess the ability to produce biomethane under the action of in-situ microorganisms, and the cumulative production reaches up to 1.97 mL/g. The biomethane production cycle of the shales is generally 15 d. According to the metabolic model of microbial degradation of complex organic matter, the methanogenesis process of anaerobic digestion of coal-measure shale can be divided into three stages: hydrolysis stage, hydrogen-producing acetogenic stage, and methanogenesis stage. There is an obvious positive correlation between the biomethane production and the TOC content of the shales. Especially when the TOC content is greater than 10%, the biomethane production increases significantly. Also, biomethane production is negatively correlated with the Ro. When the Ro increases to 3.78%, the shales almost no longer produce biomethane. The TOC content and Ro of the coal measure shale mainly exert their influence in the hydrolysis stage. As the TOC content decreases and Ro increases, the amino acids and other metabolites produced by the microbial digestion of shale organic matter decrease, making the concentrations of the required substrates decrease in the hydrogen production, acetate production and methanogenesis stages. Consequently, the biomethane production decreases.